The trajectory of the medial longitudinal fasciculus in the human brain: A diffusion imaging‐based tractography study. Issue 18 (1st October 2021) - Li, Mengjun; Yeh, Fang‐Cheng; Zeng, Qingrun; Wu, Xiaolong; Wang, Xu; Zhu, Zixin; Liu, Xiaohai; Liang, Jiantao; Chen, Ge; Zhang, Hongqi; Feng, Yuanjing; Li, Mingchu
Abstract: The aim of this study is to investigate the trajectory of medial longitudinal fasciculus (MLF) and explore its anatomical relationship with the oculomotor nerve using tractography technique. The MLF and oculomotor nerve were reconstructed at the same time with preset three region of interests (ROIs): one set at the area of rostral midbrain, one placed on the MLF area at the upper pons, and one placed at the cisternal part of the oculomotor nerve. This mapping protocol was tested in an HCP‐1065 template, 35 health subjects from Massachusetts General Hospital (MGH), 20 healthy adults and 6 brainstem cavernous malformation (BCM) patients with generalized q‐sampling imaging (GQI)‐based tractography. Finally, the 200 μm brainstem template from Center for In Vivo Microscopy, Duke University (Duke CIVM), was used to validate the trajectory of reconstructed MLF. The MLF and oculomotor nerve were reconstructed in the HCP‐1065 template, 35 MGH health subjects, 20 healthy adults and 6 BCM patients. The MLF was in conjunction with the ipsilateral mesencephalic part of the oculomotor nerve. The displacement of MLF was identified in all BCM patients. Decreased QA, RDI and FA were found in the MLF of lesion side, indicating axonal loss and/or edema of displaced MLF. The reconstructed MLF in Duke CIVM brainstem 200 μm template corresponded well with histological anatomy. The MLF and oculomotor nerve were visualized accurately with our protocol using GQI‐based fiber tracking. This GQI‐based tractography is an important tool in the reconstruction and evaluation of MLF. Abstract : The mapping protocol of medial longitudinal fasciculus using the generalized q‐sampling imaging based tractography.